India : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper discusses various aspects of goods and service tax (GST) on India's tax policy. Dual rate structure with a low standard rate and an additional higher rate on select items can be progressive and preserve revenue neutrality, while streamlining exemptions would further contribute to progressivity and reduce compliance and administrative costs. Simplifying the GST is possible without imposing a significantly higher burden on the poor. There are likely significant benefits from lower costs of compliance and administration. The literature on value added tax (VAT) compliance costs shows that there is broad variation across countries; however, there is a consensus that compliance costs are regressive and administrative costs increase with complexity. While evidence on India is nascent and remains to be assessed as experience with the GST is gained, anecdotal evidence from large firms indicates sizable increases in costs, which may be even more burdensome for smaller firms. Streamlined rates would also weaken incentives to lobby for lower rates.